The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1259/bjr/62779246
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation inT1of healthy human articular cartilage of the knee joint

Abstract: ABSTRACT. The longitudiual relaxation time T 1 of native cartilage is frequently assumed to be constant. To redress this, the spatial variation of T 1 in unenhanced healthy human knee cartilage in different compartments and cartilage layers was investigated. Knees of 25 volunteers were examined on a 1.5 T MRI system. A three-dimensional gradient-echo sequence with a variable flip angle, in combination with parallel imaging, was used for rapid T 1 mapping of the whole knee. Regions of interest (ROIs) were defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
6
16
0
Order By: Relevance
“…Previously, it has been assumed that T 1 of native cartilage is relatively constant (11, 26). However, more recent studies both in vitro and in vivo support our findings (27, 28). Generally, water content of articular cartilage is considered more related to T 2 relaxation time (29–31).…”
Section: Discussionsupporting
confidence: 87%
“…Previously, it has been assumed that T 1 of native cartilage is relatively constant (11, 26). However, more recent studies both in vitro and in vivo support our findings (27, 28). Generally, water content of articular cartilage is considered more related to T 2 relaxation time (29–31).…”
Section: Discussionsupporting
confidence: 87%
“…The exact nature of this relationship is unclear, but is believed to relate more to the PG content of the tissue than the collagen architecture [16]. A systematic survey of native T 1 in different cartilage compartments of healthy human volunteers was undertaken by Wiener et al [17]. In this study, T 1 values were shown to decrease from the superficial cartilage layers to the deep layer, consistent with the dependence of native T 1 values upon the macromolecular construction of cartilage.…”
Section: Mri Of Cartilagesupporting
confidence: 65%
“…T1, T1r, T2, and T2* relaxation times displayed concordant regional and zonal changes upon loading. In the unloaded state, T1 values were found to be quite variable, which has been demonstrated before (30). T1 relaxation time is considered more related to the PG than to the collagen content, although the exact biochemical correlate remains unclear (31).…”
Section: Discussionmentioning
confidence: 76%